PENERAPAN PENDEKATAN REFLEKTIF DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS X TITL 2 SMK NEGERI 1 DENPASAR - Huriah Raidah S; I Nyoman Adi Susrawan; Ni Made Wersi Murtini (Bajang Institute, 2025)
This research aims to improve speaking skills using a reflective approach so that class X TITL 2 students achieve KKM. The method used in the research is classroom action research carried out in two cycles. Each cycle consists of planning, implementation, observation, reflection and decision stages. The first cycle held 2x meetings, while in the second cycle there were 3x meetings. The subjects in this research were students of class The reflective approach is carried out using reflective sheets, so that students can freely express their thoughts and feelings regarding learning in class. The research results are an indicator of success in this research seen from learning completeness of 75%. Students who achieved a minimum completion criteria score of 70. From the research results in cycle I, students who had achieved the KKM were 58%, with an average score of 6.96 and in cycle II learning outcomes increased by 88.5% with an average score of 10.62, so the increase was 30%. Based on the results of this research, it can be concluded that student learning outcomes on the concept of student speaking ability can be improved through a reflective approach